VERIFICATION OF UNIVERSITY CLASS OF DIFFERENT CRITICAL EXPONENTS FOR COMPETITIVE GROWTH MODEL IN 1+1 DIMENSION (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
In this work we have reported the evolution of rough surface by different competitive growth model in 1+1 dimension. The competition has mainly been made between Random Deposition- Ballistic Deposition (RD-BD) and Random Deposition with Surface Relaxation-Ballistic Deposition (RDSRBD) model. The influence of a typical growth mechanism on the critical time and interface width has been studied in detail by varying the fractional values (p) for a typical model. Different parameters like roughness exponent, growth exponent or velocity of the surface growth have been studied and a typical dependence of all these parameters on phas been found and reported for the first time. It has been found that unlike the previously reported result the growth cannot be described by any single mechanism even for the pure RD, RDSR or BD model rather there exists two distinct crossover times and thus it may be best described by linear combinations of two different growth models.